2022
DOI: 10.1136/bmjopen-2022-062535
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration and noise exposure with hearing loss among Chinese and American adults: two cross-sectional studies

Abstract: ObjectivesTo examine the associations of sleep duration (SPD) and noise exposure with hearing loss (HL) among Chinese and American adults.DesignTwo cross-sectional studies.SettingThe National Health and Nutrition Examination Survey (2011–2012), and Zhejiang Chinese participants between 1 January 2018 and 1 November 2021.Participants3322 adults from the USA and 4452 adults from Zhejiang, China.Main outcome measuresHL was defined as a pure-tone average >20 dB in the better ear at low frequency (500, 1000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…The associations were independent of gender, age, marital status, education level, area of residence, smoking status, drinking status, BMI, social participation, baseline health condition and sleep quality. A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The associations were independent of gender, age, marital status, education level, area of residence, smoking status, drinking status, BMI, social participation, baseline health condition and sleep quality. A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…A few population-based studies provided insights into the heterogeneous effects of nocturnal sleep duration (26)(27)(28)(29). Some studies reported that long duration of nocturnal sleep could be a sign of high HL risk (26,27). A recent article revealed an association between nocturnal sleep with ≤ 4 h (OR: 1.53, 95%CI: 1.31, 1.80) and HL in comparison to the 7 h group (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both sleep deprivation and excessive sleep are associated with VI ( 12 ). A study conducted among Chinese individuals indicated that a daily sleep duration ≥8 h is significantly associated with HI ( 13 ). Similarly, a study involving 632 individuals aged ≥70 years reported that a sleep duration of >8 h is associated with increased hearing thresholds ( 14 ).…”
Section: Introductionmentioning
confidence: 99%